Defence doctrines and conversion - Møller, Bjørn; Voronkov, L.S. (Lev Sergeevich) (Dartmouth, 1996)
This work contains the contributions to the workshop on conversion, held under the auspices of the second conference of the European Peace Research Association (EUPRA) on "Improving European Security: Threats and Responsibilities", held in Budapest, 11-14 November 1993.